Pemikiran Ekonomi Ibnu Al-Qayyim al-Jauziyyah - Umari, zuul fitriani (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This article uses a review of the literature on medieval Arab professor/ economic thought Syamsuddin Abdullah Muhammad bin Abi Bakr Al Zar'i or known as Ibn Qayyim. An approach that focuses on explaining how the concept of usury is in the view of Ibn al-Qayyim al-jawziyyah. as a master of theology and translator of Islamic scriptures, he was one of the leading jurists from the Hambali school in four schools of Islamic law that emerged between the eighth and fourteenth centuries (after the other three, Hanafi, Maliki and Syafii, respectively, the names were pioneers ) There are economic ideas discussed, namely: Islamic economic philosophy, comparison and difference between wealth and poverty, economic interests of zakat, interest in usury al-fadl and riba al-nasi'ah, market mechanisms and the need for public sector intervention.